Relationship between Selected Serum Metallic Elements and Obesity in Children and Adolescent in the U.S. - Fan, Yun (Nutrients, 2017)
The prevalence of obesity has increased at an alarming rate worldwide. Metallic elements are involved in the pathogenesis of obesity and related diseases. To date, whether environmental exposure to metallic elements has effects on obesity in children and adolescents is still unclear. The aim of the current study was to investigate the association of blood metallic elements with obesity in U.S. children and adolescents. This cross-sectional study was performed with 5404 children and adolescents (6–19 years, 2745 males and 2659 females) who participated in the US National Health and Nutrition Examination Survey 2011–2014. Blood lead, mercury, selenium, manganese, copper, and zinc, as well as biochemical parameters including triglyceride (TG), cholesterol, low-density lipoprotein (LDL), and homeostasis model assessment of insulin resistance (HOMA-IR) were assessed for all subjects. Multivariate logistic regression and linear regression were applied to assess associations of metallic elements and overweight, obesity status, and serum metabolites as distinct outcomes adjusted for age, gender, ethnicity, and the poverty income ratio. When stratified by age and sex, significant associations were found between the highest quartile of copper concentrations in blood with obesity status (OR = 9.27, 95% CI: 5.43, 15.82, p(for trend) < 0.001) and cholesterol (OR = 3.08, 95% CI: 1.43, 6.63, p(for trend) < 0.001). The highest concentrations of manganese in the blood was associated with obesity in those aged 6–19 years (OR = 2.29, 95% CI: 1.74, 3.02, p(for trend) < 0.001). Moreover, blood mercury and selenium showed positive relationships with cholesterol. Further, a negative association existed between blood zinc and obesity. The National Health and Nutrition Examination Survey data provide epidemiological evidence that blood metallic elements are positively associated with obesity in children and adolescents. However, the underlying mechanisms still need further exploration.